Pengaruh Kualitas Pelayanan dan Penetapan Harga Terhadap Loyalitas Konsumen Pada Sop Tunjang Dwi Group LIrik Ind_ragiri HUlu - Kinanti Suwarno; Endang Sutrisna (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the effect of service quality and pricing on consumer loyalty. The method used in this research is descriptive and quantitative statistics with a sample of 100 respondents and using accidental sampling technique. The data sources in this study came from primary data obtained from distributing questionnaires and statistically tested with the SPSS program and secondary data using target data and 2017-2021 sales realization. Data analysis technique used is quantitative analysis using validity test, reliability test and linear regression analysis. The test results in this study indicate that partially the service quality variable (X1) has a positive effect on consumer loyalty (Y). partially the pricing variable (X2) has a positive effect on consumer loyalty (Y). And simultaneously service quality (X1) and pricing (X2) have a positive effect on consumer loyalty (Y). Keywords: service quality, pricing; consumer loyalty